New musical figurations: Anthony Braxton's cultural critique - Radano, Ronald M. (Chicago The University of Chicago Press, 1993)
New Musical Figurations exemplifies a dramatically new way of configuring jazz music and history. By relating biography to the cultural and musical contours of contemporary American life, Ronald M. Radano observes jazz practice as part of the complex interweaving of postmodern culturea culture that has eroded conventional categories defining jazz and the jazz musician. Radano accomplishes all this by analyzing the creative life of Anthony Braxton, one of the most emblematic figures of this cultural crisis.Born in 1945, Braxton is not only a virtuoso jazz saxophonist but an innovative theoretician and composer of experimental art music. His refusal to conform to the conventions of official musical culture has helped unhinge the very ideologies on which definitions of "jazz," "black music," "popular music," and "art music" are founded.New Musical Figurations gives the richest view available of this many-sided artist. Radano examines Braxton's early years on the South Side of Chicago, whose vibrant black musical legacy inspired him to explore new avenues of expression. Here is the first detailed history of Braxton's central role in the Association for the Advancement of Creative Musicians, the principal musician-run institution of free jazz in the United States. After leaving Chicago, Braxton was active in Paris and New York, collaborating with Philip Glass, Steve Reich, Frederic Rzewski, and other composers affiliated with the experimental-music movement. From 1974 to 1981, he gained renown as a popular jazz performer and recording artist. Since then he has taught at Mills College and Wesleyan University, given lectures on his theoretical musical system, and written works for chamber groups as well as large, opera-scale pieces.The neglect of radical, challenging figures like Braxton in standard histories of jazz, Radano argues, mutes the innovative voice of the African-American musical tradition. Refreshingly free of technical jargon, New Musical Figurations is more than just another variation on the same jazz theme. Rather, it is an exploratory work as rich in theoretical vision as it is in historical detail.